Chapter Transposition of the Motif of the Triad of Inseparable Virtues in the Polish Literature of Positivism and Young Poland - Mazan, Bogdan (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
Response of the Polish positivist and modernist writers to the biblical triad: faith, hope, and love has been the focal point of my research project. My aim was to trace a representative variety of references to these three motifs, both in their historical and timeless dimension. I was particularly concerned with outstanding, but all too often forgotten literary texts. A combination of traditional and contemporary research methods and critical approaches were used, such as hermeneutic fusion of cognitive horizons, intertextuality, and comparative cultural studies. My research brought to light numerous literary responses to faith, hope and love, of various artistic value, dealing mostly with basic human affairs but also with reactions reaching deeply into transcendence.